2015
DOI: 10.1371/journal.pbio.1002130
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Non-Indigenous Species Based on Their Impacts: Considerations for Application in Marine Management

Abstract: Assessment of the ecological and economic/societal impacts of the introduction of non-indigenous species (NIS) is one of the primary focus areas of bioinvasion science in terrestrial and aquatic environments, and is considered essential to management. A classification system of NIS, based on the magnitude of their environmental impacts, was recently proposed to assist management. Here, we consider the potential application of this classification scheme to the marine environment, and offer a complementary frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
145
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 61 publications
(71 reference statements)
0
145
0
Order By: Relevance
“…Further research is needed to better understand the impacts of invasive alien species on marine ecosystems and to adopt management strategies accordingly (Ojaveer et al, 2015). Relevant experimental studies are lacking for most invasive alien species (Katsanevakis et al, 2014), while scientific effort is unevenly distributed (as also found in our review, i.e., a bias toward the areas with the greatest concentration of research institutions in Europe and North America) with important gaps in many regions and taxonomic groups.…”
Section: Biological Invasions and Conservation Planning In The Marinementioning
confidence: 84%
See 1 more Smart Citation
“…Further research is needed to better understand the impacts of invasive alien species on marine ecosystems and to adopt management strategies accordingly (Ojaveer et al, 2015). Relevant experimental studies are lacking for most invasive alien species (Katsanevakis et al, 2014), while scientific effort is unevenly distributed (as also found in our review, i.e., a bias toward the areas with the greatest concentration of research institutions in Europe and North America) with important gaps in many regions and taxonomic groups.…”
Section: Biological Invasions and Conservation Planning In The Marinementioning
confidence: 84%
“…As a consequence, the eradication of established invasive alien species, which is sometimes a sensible option in terrestrial systems, becomes difficult in freshwater systems and seems almost impossible in marine ones. While several successful eradication attempts in the terrestrial and the freshwater realms (especially in isolated or confined areas) have been made, marine attempts have mostly failed (Ojaveer et al, 2015), unless at a very initial stage of invasion, e.g., the eradication of Caulerpa taxifolia in California (Anderson, 2005) or of the black-striped mussel Mytilopsis sallei in Australia (Willan et al, 2000). Marine alien species are an unavoidable new component of the ecosystems and cannot be ignored.…”
Section: Biological Invasions and Conservation Planning In The Marinementioning
confidence: 99%
“…To this end, recent work has offered a system for classifying alien species based on the magnitude of their ecological impacts (Blackburn et al 2014, Hawkins et al 2015. However, this progressive framework remains reliant on the primary studies that document impact, but such studies are surprisingly seldom undertaken for marine alien species (Simberloff et al 2013, Ojaveer et al 2015a, Ojaveer et al 2015b. Further, many existing impact studies tend to be unevenly distributed among geographic regions, different taxa and study systems (Pysek and Richardson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on invasive species (Pysek et al 2008), leaving the impacts of many other species unquantified, especially in regions where they have not transitioned from alien to invasive status (sensu Blackburn et al 2011). Whilst these gaps in knowledge are understandable as they reflect an uneven distribution of specialist researchers, research funds and research impetus, they hinder appropriate and effective management of invasions (Ojaveer et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…This literature search was performed using the following key words: aquatic, pest, management, removal, eradication, species. Citations in topical review papers and books were also examined (Meronek et al 1996, Veitch & Clout 2002, Halfyard 2010, Kolar et al 2010, Britton et al 2011, Loppnow et al 2013, Ojaveer et al 2015. I also performed a secondary literature search to look for evidence of density-dependent recruitment for each species that was a target of removal in the case studies.…”
Section: Literature Searchmentioning
confidence: 99%